XRF data and tie points from IODP Site U1478, Mozambique Channel, SW Indian Ocean - Koutsodendris, Andreas (PANGAEA, 2020)
This dataset presents the XRF core-scanning record from International Ocean Discovery Program (IODP) Site U1478 off the Limpopo River mouth (Mozambique Channel, SW Indian Ocean) spanning the past c. 4 Ma. Site U1478 was drilled in the northernmost Natal Valley, on the Inharrime Terrace (25°49.26′ S; 34°46.16′ E) at a water depth of 488 m below sea level. The XRF core scanning of the ~257-m-long splice for Site U1478 was carried out using an Itrax Core Scanner at Lamont-Doherty Earth Observatory Core Repository, Columbia University (USA). In total, 239 sections (archive halves) were scanned at a voltage of 30 kV and a tube current of 55 mA using a Cr tube and employing an exposure time of 2 seconds. Measurement spacing was set at 2 mm, with downcore and crosscore slit sizes set at 2 mm and 2 cm, respectively. The individual element counts were normalized using the ratio of raw total counts of a given element to the total counts of all processed elements for the respective measurement position. To eliminate non-linear matrix effects and constant-sum constraints, log ratios were applied on the elemental ratios. The age model of Site U1478 is based on cyclostratigraphic analysis of the XRF-based log(Ti/Ca) record and its tuning to ice-volume, precession and eccentricity cycles.